Benign Cystic Mesothelioma: A Rare Cause for Scrotal Swelling - A. Aber; A. Tahir; V. Arumuham; G. Smith; S. Almpanis (Case Reports in Medicine)
Benign cystic mesothelioma of the tunica vaginalis is a rare occurrence. It usually presents with painless gradual swelling in the scrotum. These types of benign mesotheliomas typically occur in the peritoneum and usually affect young to middle-aged patients. We present in this case an unusual case of benign cystic mesothelioma of the tunica vaginalis in a 77-year-old male patient.